Nano-soy-protein microcapsule-enabled self-healing biopolyurethane-coated controlled-release fertilizer: preparation, performance, and mechanism. (June 2021) - Yu, Z.; Yang, Y.; Wang, C.; Shi, G.; Xie, J.; Gao, B.; Li, Y.C.; Wan, Y.; Cheng, D.; Shen, T.; Hou, S.; Zhang, S.; et al.
Abstract: Although various eco-friendly and sustainable biobased polyurethane-coated controlled-release fertilizers (BPCFs) have been developed, their applications were limited by the bio-based coating contained many microscopic holes. In this work, a nano-soy-protein microcapsule-enabled self-healing biopolyurethane-coated controlled-release fertilizer (NSBCF) with enhanced controlled-release performance was fabricated. Nanoscale soy-protein microcapsules (SMCs) were prepared from soy-protein isolate (SPI) and poly (lactic-co-glycolic acid) using the water-oil-water emulsification technology. The self-healing biopolymer coatings of NSBCF with uniformly dispersed SMCs were constructed through self-assembly. The controlled-release longevity of NSBCF was >28 days longer than that of the BPCF with the unmodified coating. The self-healing mechanism of NSBCF was determined by directly observing the restoration area and the 3D pore distribution of coating using fluorescence labeling and X-ray computed tomography. After being released from the SMCs, SPI self-repaired the coating by reacting with glutaraldehyde to form solid resins to clog the microscopic holes. The SMCs-enabled self-healing process successfully reduced the nutrient release rate and extended the nutrient release longevity of NSBCF. This novel biobased controlled-released fertilizer with self-healing function represents a new direction for the development of high efficiency and environmentally friendly fertilizers to improve agriculture and food sustainability. Graphical abstract: Image 1 Highlights: Biobased controlled-release materials are inexpensive, non-toxic, renewable, and biodegradable. Dual controlled-release modified self-healing technology improves the controlled-release characteristics. SMCs can released repair agent to heal the coating endows the coating with the ability to self-healing.